Exchange rates and transition economies' export prices: Is there evidence for pricing-to-market behavior? - Emilia Penkova (Universität Dortmund, Wirtschafts- und Sozialwissenschaftliche Fakultät, 2005)
The paper tests for potential pricing-to-market for a wide range of export industries in selected transition economies, namely Poland, Hungary and Bulgaria, at the four-digit level over the period 1990-1998. Panel estimation is undertaken and a fixed-effects linear model is estimated. The empirical evidence reported here offers new evidence for transition economies that have not been investigated before. Given the industries sampled, more price discrimination across destination is observed in Bulgaria than in Poland and Hungary. There is no evidence showing pricing-to-market in relation to common industries across source countries.
Keywords: C23; F14; P20; 330; pricing-to-market; transition economies; panel data